Make change work : staying nimble, relevant, and engaged in a world of constant change - Pennington, Randy (John Wiley & Sons, Inc., 2013)
Remain competitive, inspire innovation, and ensure success Constantly adapting, improving, and changing is more important than ever for companies to remain competitive in today's marketplace. Make Change Work presents real solutions to thriving in a world of constant change. This book educates managers and leaders on how to lead change, with strategies for creating urgency, building support, and ensuring successful change. Get the guidance you need to be bold in the face of change, and learn how to make your company faster, better, cheaper, and friendlier-by simply liste.